2020
DOI: 10.6018/cpd.352791
|View full text |Cite
|
Sign up to set email alerts
|

Composición e invarianza factorial del Autoinforme de Barreras para la Práctica de Ejercicio Físico (ABPEF-M) en universitarios mexicanos deportistas

Abstract: El presente estudio analiza las propiedades psicométricas propuestos por Rodríguez-Villalobos, Viciana, Tristán y Blanco (2017) para el Autoinforme de Barreras para la Práctica de Ejercicio Físico (ABPEF-M) en hombres y mujeres deportistas universitarios. La muestra total fue de 413 universitarios mexicanos deportistas 174 mujeres y 239 hombres, con edades comprendidas entre 18-26 años (M = 20.76; DE = 2.06). La estructura factorial del cuestionario se analizó mediante análisis factoriales confirmatorios. Los … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This scale was also used by Frederick et al (2022), who recruited enrolled university students and excluded university athletes from their analysis. Mondaca Fernández et al (2020) selected Mexican university students who practised a sport and regularly participated in tournaments and/or sports competitions. They did not report significant differences between women and men in relation to the four factors of the Mexican version of the ABPEF that were studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This scale was also used by Frederick et al (2022), who recruited enrolled university students and excluded university athletes from their analysis. Mondaca Fernández et al (2020) selected Mexican university students who practised a sport and regularly participated in tournaments and/or sports competitions. They did not report significant differences between women and men in relation to the four factors of the Mexican version of the ABPEF that were studied.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with other studies on university students in which women were found to have greater barriers (Bisquert Bover et al, 2020; Blanco Ornelas et al, 2019; Gómez-López et al, 2010; Ramírez-Vélez et al, 2014; Sevil Serrano et al, 2017; Thomas et al, 2019). However, some studies have not identified gender-based differences in perceived barriers among young adults (Chan, 2014; Frederick et al, 2022; Mondaca et al, 2020). The differences between our findings and those of Chan (2014) and Frederick et al (2022) may be explained by variations in study methodology and the students’ field of study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation